Stakeholder Characteristics in the Pentahelix Model for Digital Integrated Farming Communities Koper-Tani - Kumbara Kumbara; Silfia Silfia; Roni Afrizal (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
The agricultural sector in Indonesia still faces various individual challenges with multiple roles, limited market access, low supply chain transparency, and minimal adoption of digital technology that can improve the efficiency of farming businesses. Digitalization of integrated farming communities is a potential solution to overcome these challenges. This study aims to analyze the characteristics and roles of stakeholders in the pentahelix model for the development of digital farming communities. The research method employs a qualitative descriptive approach, utilizing hybrid survey techniques (online and offline) to collect data from 60 respondents across various regions. Data were analyzed using qualitative descriptive methods with data visualization techniques. The analysis stages consist of: reduction (selection of relevant data), visualization by grouping each component of the question interpreted in the form of a percentage, drawing conclusions to state the dominant factors and implications based on stakeholder characteristics, and determining their roles in the form of a pentahelix model. The study's results showed that the majority of stakeholders possess characteristics that are ready to adopt digital technology, with the primary needs being market access, increasing farmer capacity, and environmental sustainability. The characteristics of the pentahelix model involve Farmer Business Actors, Consumer Society, Academics and/or Agricultural Practitioners, Government, and the Koper-Tani Media Platform, which plays a crucial role in supporting the development of integrated digital farming communities.